URGENSI HIKMAH DALAM PERGERAKAN DAKWAH DI QUR’AN SURAT AN-NAHL AYAT 125 - Nisa Amci Ilzania; Sunardi Bashri Iman (Al Kareem Jurnal Ilmu Al Qur'an dan Tafsir, 2024)
At this point, the perpetrators of terrorism and radicalism have entered the Muslim community, making it harder to preach. Therefore, a moderate narrative is necessary, and the method of the narrative with wisdom is the answer, as mentioned in the An-Nahl verse 125. "What is the urgency of the way of wisdom in the movement of worship in Indonesia?" is the formula of the problem of this writing. This research is a qualitative descriptive library study that looks at the value and importance of wisdom in the movement of the prophet. This research data source consists of books of interpretation related to the interpretation of verse 125 of Surat An-Nahl, and scientific articles related to this research theme. The author finds that wisdom is an acceptable way to solve problems related to the above verse.